2015
DOI: 10.3390/w7073486
|View full text |Cite
|
Sign up to set email alerts
|

Science-Based IWRM Implementation in a Data-Scarce Central Asian Region: Experiences from a Research and Development Project in the Kharaa River Basin, Mongolia

Abstract: Abstract:Mongolia is not only a water-scarce but also a data-scarce country with regard to environmental information. At the same time, regional effects of global climate change, major land use changes, a booming mining sector, and growing cities with insufficient and decaying water and wastewater infrastructures result in an increasingly unsustainable exploitation and contamination of ground and surface water resources putting at risk both aquatic ecosystems and human health. For the mesoscale (≈15,000 km 2 )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Kaus et al International Review of Hydrobiology 2016, 101, 147-159 within their home range is valuable for authorities to help evaluate both spatial and temporal management strategies, particularly as river networks in north and central Asia are becoming progressively polluted and fragmented, and the impacts of climate change on continental river systems (e.g. In this taimen biotelemetry study, the first to be conducted on an Amur River basin population, a substantial data set was obtained and seasonal home range sizes and individual behaviour patterns within and between the Onon River and a major tributary were identified, thus helping to fill an important knowledge gap for regional conservation of this endangered species and river basin management in data-scarce Mongolia (Karthe et al, 2015b). In this taimen biotelemetry study, the first to be conducted on an Amur River basin population, a substantial data set was obtained and seasonal home range sizes and individual behaviour patterns within and between the Onon River and a major tributary were identified, thus helping to fill an important knowledge gap for regional conservation of this endangered species and river basin management in data-scarce Mongolia (Karthe et al, 2015b).…”
Section: Discussionmentioning
confidence: 99%
“…Kaus et al International Review of Hydrobiology 2016, 101, 147-159 within their home range is valuable for authorities to help evaluate both spatial and temporal management strategies, particularly as river networks in north and central Asia are becoming progressively polluted and fragmented, and the impacts of climate change on continental river systems (e.g. In this taimen biotelemetry study, the first to be conducted on an Amur River basin population, a substantial data set was obtained and seasonal home range sizes and individual behaviour patterns within and between the Onon River and a major tributary were identified, thus helping to fill an important knowledge gap for regional conservation of this endangered species and river basin management in data-scarce Mongolia (Karthe et al, 2015b). In this taimen biotelemetry study, the first to be conducted on an Amur River basin population, a substantial data set was obtained and seasonal home range sizes and individual behaviour patterns within and between the Onon River and a major tributary were identified, thus helping to fill an important knowledge gap for regional conservation of this endangered species and river basin management in data-scarce Mongolia (Karthe et al, 2015b).…”
Section: Discussionmentioning
confidence: 99%
“…A meaningful set-up with regard to spatial sampling strategies, analytical methods and potential biological indicator species may be derived from the results of the current study. In a broader context, the data presented here has filled an important knowledge gap for integrative water resource management planning, which in the case of the KRB has typically been impeded by poor data availability (Karthe et al 2015b). For the first time in the KRB or anywhere in Mongolia, it has been shown that heavy metal emissions related to gold mining activities are not only theoretical risks, but that accumulation from the environment into consumed fish species is evident and has reached concerning levels in the worst affected regions e.g.…”
Section: Discussionmentioning
confidence: 98%
“…Today, key challenges for the implementation of the IWRM and nexus concepts include (a) outdated infrastructures in the water, irrigation/food production and energy sectors, (b) transboundary disputes, (c) data scarcity, (d) capacity deficits in various parts of the water sector and (e) inefficient governance structures. While the complexity of water problems is already challenging in the world's most developed countries, in Central Asia the latter three aspects are additional obstacles for water management planners (Dombrowsky et al 2014;Ibisch et al 2016b;Karthe et al 2015b;Kirschke et al 2017).…”
Section: Water Usage and Managementmentioning
confidence: 99%
“…On the implementation side, a specific focus has been on holistic concepts such as Integrated Water Resources Management and the food-waterenergy nexus (Guillaume et al 2015;Ibisch et al 2016a;Jalilov et al 2015;Karthe et al 2015b), which lie at the core of most national water management strategies of the region. Advances in water management increasingly require a sound scientific basis, which over the past decade was covered not only by several books and thematic issues in international journals, but also by the emergence of a specific journal focusing on water management in the Central Asian region (Table 1).…”
Section: Introductionmentioning
confidence: 99%